Methylation of the Vitamin D Receptor (VDR) Gene, Together with Genetic Variation, Race, and Environment Influence the Signaling Efficacy of the Toll-Like Receptor 2/1-VDR Pathway - Meyer, Vanessa; Saccone, Donovan Sean; Tugizimana, Fidele; Asani, Furaha Florence; Jeffery, Tamsyn Jacki; Bornman, Liza (Frontiers in Immunology, 2017)
Background The disparity in prevalence of infectious diseases across the globe is common knowledge. Vitamin D receptor (VDR)-mediated toll-like receptor (TLR) 2/1 signaling produces antimicrobial peptides, which is critical as a first line of defense in innate immunity. Numerous studies disclosed the independent role of genetic polymorphisms in this pathway, vitamin D status or season and more recently epigenetics, as factors contributing to infectious disease predisposition. Few studies address the interaction between environment, genetics, and epigenetics. Here, we hypothesized that VDR-mediated TLR2/1 signaling is influenced by a combination of environment, epigenetics and genetics, collectively influencing differential innate immunity. Methods Healthy Black and White South Africans (n = 100) donated blood, while ultraviolet index (UVI) was recorded for the duration of the study. LC-MS/MS supported 25(OH)D3 quantification. Monocyte/macrophage cultures, supplemented with/without 1,25(OH)2D3, were activated with the TLR2/1 elicitor, Pam3CSK4. VDR, cathelicidin antimicrobial peptide, hCAP-18, and 25-hydroxyvitamin D3-24-hydroxylase expression were quantified by RT-qPCR or flow cytometry. Pyrosequencing facilitated VDR methylation analysis and single-nucleotide polymorphism (SNP) genotyping in regions pinpointed through a bioinformatics workflow. Results Season interacted with race showing 25(OH)D3 deficiency in Blacks. UVI correlated with 25(OH)D3 and VDR methylation, likely influencing race differences in the latter. Regarding the TLR2/1 pathway, race differences in SNP genotype distribution were confirmed and functional analysis of VDR-mediated signaling showed interaction between race, season, and 25(OH)D3 status. Multivariate OPLS-DA mirrored several interactions between UVI, 25(OH)D3 status, DNA sequence, and methylation variants. Methylation of the third cytosine-phosphate-guanine dinucleotide (CpG) in the promoter CpG island (CGI) 1062, CGI 1062 CpG 3, significantly discriminated a 5.7-fold above average mean in VDR protein level upon TLR2/1 elicitation, the variation of which was further influenced by 25(OH)D3 status and the VDR SNP TaqI. Conclusion Regulation of VDR-mediated TLR2/1 signaling is multifactorial, involving interaction between environment [UVI and consequent 25(OH)D3 status], epigenetics (VDR methylation at key regulatory sites), and genetics (TLR1, TIRAP, and VDR SNPs).